2019
DOI: 10.2217/cer-2018-0150
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of acute public hospitals in the region of Murcia, Spain

Abstract: Aim: To evaluate the level of efficiency of public acute hospitals situated in the region of Murcia (Spain). Materials & methods: Data from nine acute general hospitals of Murcia’s Health Service (SMS by its Spanish acronym) were analyzed over the 2012–2014 period. The data were extracted from the In-patient Health Establishment Statistics of the Ministry of Health, Social Services and Equality, from the National Health Service (SNS) portal and the SMS portal. To this end, the data envelopment analysis (DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Therefore, it is reasonable and necessary to use the improved three-stage DEA method when measuring the efficiency of public hospitals for accurate results. The results for efficiency indicated that the mean efficiency score of public hospitals in Guangdong was 0.891, which was higher than that in Palestine (0.853) [32], Serbia (0.782) [45], Turkey (0.724) [69], Saudi Arabia (0.76) [50], Jordan (0.547) [70], and Iran (0.873) [71] and lower than that in Spain (1.016) [72], Wuhan, China (0.899) [73], and Taiwan, China (0.973) [74]. Only 38.1% of cities were found to be efficient in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable and necessary to use the improved three-stage DEA method when measuring the efficiency of public hospitals for accurate results. The results for efficiency indicated that the mean efficiency score of public hospitals in Guangdong was 0.891, which was higher than that in Palestine (0.853) [32], Serbia (0.782) [45], Turkey (0.724) [69], Saudi Arabia (0.76) [50], Jordan (0.547) [70], and Iran (0.873) [71] and lower than that in Spain (1.016) [72], Wuhan, China (0.899) [73], and Taiwan, China (0.973) [74]. Only 38.1% of cities were found to be efficient in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…First, the hospital efficiency in different countries or regions is discussed by using the classical DEA method from the microcosmic level. Kawaguchi et al [ 9 ], Sohn et al [ 10 ], Chowdhury et al [ 11 ], Gholami et al [ 12 ], Flokou et al [ 13 ], Blatnik et al [ 14 ], Campanella et al [ 15 ], and Fuentes et al [ 16 ] respectively evaluated the hospital efficiency of developed countries or regions, namely Japan, South Korea, the United States, Ontario, Greece, Slovenia, Italy, and Murcia of Spain. Jat et al [ 17 ] and Gimenez et al [ 18 ] assessed the hospital efficiency of the developing countries India and Colombia.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we compare traditionally managed public hospitals, public hospitals managed by a private finance initiative (PFI. The expenditure of goods and services commonly referred as hospital operational costs (Fuentes et al, 2019). Operational costs often included in the productivity analysis which can show good comparisons in terms of units and time (Anthun et al, 2017(Anthun et al, )1999(Anthun et al, -2014 This period was characterized by a large ownership reform with subsequent hospital reorganizations and mergers.…”
Section: (4) Operational Costmentioning
confidence: 99%
“…Many articles use the term "discharged patient" to represent the number of inpatients (Li & Dong, 2015;Narcı et al, 2015;Jiang et al, 2016;Jia & Yuan, 2017;Li et al, 2017;Giancotti et al, 2018;Kiani et al, 2018;Zhang et al, 2018;Zheng et al, 2018;Fuentes et al, 2019;Miguel et al, 2019;Jing et al, 2020). From patients who have been discharged, it can shows how was the capacity of services that have been used (Li et al, 2017).…”
Section: (1) the Number Of Inpatientsmentioning
confidence: 99%
See 1 more Smart Citation